Calculation of Saturation Magnetization and Crystal Lattice Stress for Dy₃Fe₅O₁₂ - منار ميا; بدر الأعرج; إبراهيم علي (Latakia University Journal -Basic Sciences Series, 2023)
In this article, we have studied some magnetic properties of garnet ferrite Dy₃Fe₅O₁₂. Where we calculated the total magnetic moment of the sample under study. We performed calculations on saturation magnetization. Moreover, we applied a gravimetric stress to the sample and then determined the greatest and lowest stress experienced by crystalline levels depending on the diazotization of the tensor stress elements. We reached a maximum stress of 24.0000N/cm2 when a weight of 4kg is applied to the sample face, and the lowest stress is 6.3431N/cm2.